Isolation of Brucella canis from a human sharing her house with infected dogs. - Olivera, Martha; Di Lorenzo, Cecilia (Colombia Medica, 2009)
Objective: To report a case of bacteremia in a woman living in close contact with dogs infected with Brucella canis. Methods: Previous written consent of the woman a blood sample was taken to perform rapid agglutination test, immunofluorescence, and hemoculture. Results: Brucella canis was isolated and the isolation was confirmed by the Instituto Nacional ANLIS «Carlos G. Malbran» from Argentina. The woman did not present any symptoms associated with brucellosis. Conclusion: There is a risk of contamination by B. canis for people keeping tight contact with infected dogs.